Influence of biodiesel formulation and blending to fuel properties - Mohd Faiz, A. Razak (2013)
Biodiesel is a clean burning alternative to mineral diesel fuel that is produced from renewable resources such as vegetable oil or animal fat. Vegetable oils are becoming a promising an alternative to diesel fuel because they are renewable in nature and can be produced locally and environmental friendly as well. This work presents the influence of biodiesel formulation and blending to fuel properties. Two types of biodiesel derived from rubber seed oil and waste cooking oil will be tested according to ASTM D6751 for acid value, FFA, kinematic viscosity, pour point, cloud point, density and calorific value whether as pure biodiesel or as blended with petrodiesel. Throughout these researches, it shows that the blending technique can give the solution on the alternative way to minimize the use of diesel fossil fuel in transportation. The waste cooking oil biodiesel B5 level gives the best result due to the parameter such as density, kinematic viscosity, acid value, FF A, cloud point and pour point of biodiesel almost near to the diesel fuel characteristics. Besides, the blending of rubber seed oil biodiesel B20 shows the good characteristic such as calorific value, kinematic viscosity and cold flow properties are more or less differs in 5 % than the characteristics of diesel fuel. Both biodiesel blends waste cooking oil biodiesel B5 and rubber seed oil biodiesel B20 are in the range of specification of ASTM D6751 and EN14214.